2020
DOI: 10.1155/2020/2460158
|View full text |Cite
|
Sign up to set email alerts
|

MSCs Contribute to the Conversion of Ly6Chigh Monocytes into Ly6Clow Subsets under AMI

Abstract: Background. Ly6Chigh monocytes are inflammatory cells that accumulate in an infarcted myocardium, and Ly6Clow monocytes are believed to be reparative and curb myocardial remodeling. NR4A1 is a novel target for modulating the inflammatory phenotype of monocytes during atherogenesis. Objectives. We aimed to investigate whether MSCs can contribute to the heterogeneity of Ly6Chigh monocytes differentiated into Ly6Clow monocytes and whether this regulation is related to nuclear receptor NR4A1. Methods. Ly6Chigh/low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 30 , 31 In contrast, Ly6C lo monocytes peak at 7 days after MI and play crucial roles in inflammatory resolution, angiogenesis, and adaptive immune response. 32 , 33 , 34 To clarify the effects of monocyte subsets, we performed DEG pathway enrichment analyses between Mo_Ly6c and Mo_Ear2 at 1 day and 7 days post‐MI, respectively. Compared with Mo_Ear2, Mo_Ly6c at 1 day post MI exhibited upregulated neutrophil migration and granulocyte chemotaxis genes, including Ly6c2, Ccl2, Ccr2, Lgals3, and Ccl9 (Figure S5A and S5B ).…”
Section: Resultsmentioning
confidence: 99%
“… 30 , 31 In contrast, Ly6C lo monocytes peak at 7 days after MI and play crucial roles in inflammatory resolution, angiogenesis, and adaptive immune response. 32 , 33 , 34 To clarify the effects of monocyte subsets, we performed DEG pathway enrichment analyses between Mo_Ly6c and Mo_Ear2 at 1 day and 7 days post‐MI, respectively. Compared with Mo_Ear2, Mo_Ly6c at 1 day post MI exhibited upregulated neutrophil migration and granulocyte chemotaxis genes, including Ly6c2, Ccl2, Ccr2, Lgals3, and Ccl9 (Figure S5A and S5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al. established a coculture model of MSCs and CX3CR1-/-Ly6Chi monocytes and found that MSCs upregulated the expression of NR4A1 in proinflammatory Ly6Chi monocytes, transforming them into patrolling Ly6Clo monocytes through direct cell-to-cell contact, thereby improving the prognosis of myocardial infarction ( 103 ). In another study on corneal inflammatory lymphangiogenesis, systemic administration of MSCs upregulated the expression of tumor necrosis factor -α-stimulated gene 6 (TSG-6).…”
Section: Crosstalk Between Mscs and Macrophages During Sepsismentioning
confidence: 99%
“…Based on previous studies, the immunomodulatory effects of MSCs on macrophages are believed to occur through at least three pathways: (1) direct cell-to-cell contact via cell-surface molecules, (2) paracrine signals generated by MSCs such as TGF-b, IDO, PGE2, and TSG-6, and (3) reprogramming in response to phagocytosis by macrophages. Liu et al established a coculture model of MSCs and CX3CR1-/-Ly6Chi monocytes and found that MSCs upregulated the expression of NR4A1 in proinflammatory Ly6Chi monocytes, transforming them into patrolling Ly6Clo monocytes through direct cell-to-cell contact, thereby improving the prognosis of myocardial infarction (103). In another study on corneal inflammatory lymphangiogenesis, systemic administration of MSCs upregulated the expression of tumor necrosis factor -astimulated gene 6 (TSG-6).…”
Section: Direct Cell-to-cell Contactmentioning
confidence: 99%
“…In mouse experiments, bone marrow-derived macrophages express high levels of lymphocyte antigen 6 complex locus C (Ly-6C) (Mossanen et al, 2016) These macrophages also have the potential to differentiate into Ly-6C low expression cells, which demonstrate high levels of matrix metalloproteinases (MMPs) capable of degrading collagen (Lu et al, 2020). However, Ly-6C high and Ly-6C low cells do not correspond one-to-one with M1 and M2 macrophages, they may represent a phenotype that is intermediate between the two (Ramachandran et al, 2012).…”
Section: Diversity and Plasticity Of Hepatic Macrophagesmentioning
confidence: 99%